MAPPING THE CONSUMERS COFFEE POWDER MANGSI COFFEE BASED ON SEGMENTING, TARGETING, AND POSITIONING IN DENPASAR CITY - I Putu Agi Pratama; Ratna Komala Dewi; Ni Putu Artini (Faculty of Animal and Agricultural Science, Diponegoro University, 2021)
Not all customers can be served by the company. Each company needs to identify marketsegments that can be served effectively by differentiating the main market segments, aiming at one ortwo segments and developing products so that there are always new breakthroughs. A company in orderto excel in competition must be able to recognize its market segment, target and product position againstits competitors. This research aims to determine the segmenting, targeting, and positioning of MangsiCoffee powder. The sampling technique used is the nonprobability sampling method that is accidentialsampling. Segmenting and targeting is done by using crosstab analysis, while positioning uses multidimensional scaling analysis and correspondence analysis. Mangsi Coffee powder market segmentationbased on the characteristics of consumers are men who are adults, graduated from tertiary education (last education), work as employees with monthly expenditure above the Denpasar City UMK in 2019(Rp. 2,553,000.00). Mangsi Coffee consumers based on psychographic segmentation tend to choosequality products and make coffee consumption habits a trend and lifestyle while Mangsi Coffeeconsumers based on segmentation of consumer behavior tend to choose products according to theirbenefits. Positioning using multi-dimensional scaling analysis (MDS) shows that, Mangsi Coffeepowder is not in one quadrant with all three competing products. The map shows that all four productsare in different quadrants. CA analysis (correspondence analysis), shows the superiority of MangsiCoffee powder products when compared with competitors' products is an attribute in terms ofpackaging. The importance of companies to pay attention to segmenting, targeting, and positioning tobe able to focus on achieving company goals and survive in fierce market competition. The strategy toincrease sales is carried out by adjusting the results of studies in research and the conditions of theMangsi Coffee company so that it can take policies that are in accordance with company goals.